SOCIAL CONSTRUCTION OF MARRIAGE ON ADULT SINGLE WOMEN - Agnes Rumondang Marpaung; Eko Hartanto (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2023)
This study aims to find out the social construction of marriage is formed in Indonesian society and the perspective of single adult women on the social construction of marriage. This study uses a qualitative method by doing interviews with single adult women who do self-actualization and get the question "when will you get married?" repeatedly, which isa manifestation of the social construction of marriage, as well as the collection of data through online observation. The results revealed that the social construction of marriage that formed in Indonesia is when someone is mature enough as in age and career, then the next life goal would be marriage. This construction arises because of the communal natureof Indonesians who feel like they have to take care of other people whose life choices are not the same as the tenet they profess. Researchers understand the interviewees based on their identity as a single woman who has more negative connotation compared to married women, as well as their choice to pursue a career is worried because of the perceived superiority of men, and also the connection with the growth of their character and the social life that influences them. Keywords: Construction; Marriage; Woman; Single.